Nurse-led intervention to improve quality of life and reduce rehospitalization in heart failure patients: A scoping review - Tobi Pitora; Rahmawati Dian Nurani; Dewin Safitri; Devi Harmita; Artanti Lathifah (Indonesian Nursing Journal, 2026)
Introduction: Heart failure (HF) remains a major global health problem, characterized by high morbidity and mortality rates. HF imposes a substantial burden on healthcare systems due to high rates of hospitalizations and the need for intensive medical care. Nurse-led interventions have been increasingly recognized for their potential to improve patient outcomes across various healthcare settings Objectives: This article aims to evaluate the effectiveness of a nurse-led intervention to improve the quality of life and reduce readmission rates in patients with heart failure. Methods: This study used the PRISMA-ScR (Preferred Reporting Elements for Systematic Reviews and Meta-Analyses) framework. Searches for primary studies in any language were conducted in electronic databases such as PubMed, ScienceDirect, EBSCO, and Scopus. The search began on July 30, 2025, and was updated on August 28, 2025. Articles were assessed using the Cochrane Risk of Bias Scale (ROB 2.0). Results: Five articles were included in this scoping review. Nurses provide tailored education that promotes medication adherence, lifestyle modification, and symptom monitoring, which together enhance self-care behavior and patient empowerment. Nurse-led interventions appear most effective at enhancing QoL, while their impact on rehospitalization depends on the intervention’s timing, duration, and intensity. Nurse-led interventions should be integrated into routine HF management, particularly during transitional care following hospital discharge, when patients are most vulnerable to readmission Conclusion: Nurse-led interventions improve QoL and show potential to reduce rehospitalization among HF patients.